2007
DOI: 10.1111/j.1471-0528.2007.01328.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in rates of postterm birth in Europe: reality or artefact?

Abstract: Objective To compare rates of postterm birth in Europe.Design Analysis of data from vital statistics, birth registers, and national birth samples collected for the PERISTAT project.Setting Thirteen European countries.Population All live births or representative samples of births for the year 2000 or most recent year available.Methods Comparison of national and regional rates of postterm birth. Other indicators (birthweight, deliveries with a non-spontaneous onset and mortality) were used to assess the validity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
4
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 37 publications
(47 reference statements)
2
60
4
11
Order By: Relevance
“…5,6 The incidence of post term pregnancy in present study is lower than the study conducted by Ingemarsson et al, Ahanya et al and by Marahatta R et al in Nepal, who reported the incidence of postdated pregnancy 8.3%, 7.6% and 4.6% respectively. [7][8][9] This lower incidence of post term pregnancy in our study may be because we do induction of labour at 40+ weeks in our centre.…”
Section: Discussioncontrasting
confidence: 61%
“…5,6 The incidence of post term pregnancy in present study is lower than the study conducted by Ingemarsson et al, Ahanya et al and by Marahatta R et al in Nepal, who reported the incidence of postdated pregnancy 8.3%, 7.6% and 4.6% respectively. [7][8][9] This lower incidence of post term pregnancy in our study may be because we do induction of labour at 40+ weeks in our centre.…”
Section: Discussioncontrasting
confidence: 61%
“…8 Despite an increasing overall number of delivery inductions, 12 the rate of early-term birth did not vary substantially, and the rate of postterm birth increased during the 20-year study period. Nevertheless, the incidences of perinatal mortality and long-term morbidity in our study population were comparable with those in 5 …”
Section: Discussionmentioning
confidence: 90%
“…The proportion of postterm birth seems to be decreasing. 8 Elevated risk for perinatal mortality and morbidity is associated with postterm birth. [9][10][11] In Finland, the rate of early-term birth is 17% to 18% and the rate of postterm birth is 4% to 5%.…”
mentioning
confidence: 99%
“…At a European level, there are good arguments for collaboration in audits of perinatal and maternal deaths and of rare events or outcomes [25][26].…”
Section: Discussionmentioning
confidence: 99%